Annual Report on Exchange Arrangements and Exchange Restrictions 2021. (Annual Report on Exchange Arrangements and Exchange Restrictions, 2022)
The AREAER provides a comprehensive description of restrictions on international trade and payments, capital controls, and measures implemented in the financial sector, including prudential measures that may affect capital flows for all IMF members. It also provides information on the classification of their exchange rate arrangements, operation of foreign exchange markets, restrictions on current international payments and transfers and multiple currency practices subject to the IMF's jurisdiction in accordance with Article VIII. Descriptions of individual member countries are available at AREAER Online.